The Effect of Project-Based Learning Model on Indonesian Language Learning Outcomes of Fifth-Grade Students at SD Inpres 6/75 Biru, Bone Regency - Hafid, Abd; Mujahidah, Mujahidah; Harisah, Febrianti (International Journal of Elementary School Teacher, 2025)
This is a quantitative research type experimental with a pre-experimental research design in the form of a one-group pretest-posttest design which aims to determine whether or not there is a significant effect of using the Project Based Learning learning model on the learning outcomes of Indonesian language class V students of SD Inpres 6/75 Biru. The variables in this study are the Project Based Learning learning model (independent variable) and Indonesian language learning outcomes (dependent variable). The population in this study were all fifth grade students of SD Inpres 6/75 Biru as many as 33 students. This study used non probability sampling technique or saturated sample. This research data collection technique is in the form of multiple choice tests. The data analysis technique of this research is descriptive statistical analysis and inferential statistical analysis. The results of this study are before using the Project Based learning model shows that the test scores obtained by students are still low with an average (mean) of 52.42, and after using the Project Based learning model the test results obtained by students increased with an average of 84.85. Based on the results of inferential analysis, the value of tcount (17.795) > ttable (2.03693) was obtained. The conclusion of the research results is that there is a significant effect of the Project Based Learning model on the learning outcomes of Indonesian language class V students of SD Inpres 6/75 Biru, Bone Regency.